في تصميم تعليم اللغة العربية على يوتيوب ADDIE تصميم - Faruq, Muh.; Sari, Risna Rianti; Syarofah, Alfiatus (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This research provided the description of the application of the ADDIE model in designing Arabic learning on Youtube. The fact is that there had been many developments in Arabic learning using Youtube, but several Youtube channels that provide Arabic learning content in Indonesia had not provided more experience for their users. This caused users reluctant to learn Arabic through Youtube. For this reason, it is necessary to redesign it by taking into account user needs and available resources. This type of research is R&D with the ADDIE model. After going through each stage in the ADDIE model, the results showed that users of the Youtube channel for learning Arabic, who are on average 15 to 30 years old, had an instant character in learning, they don't like content with long duration, focused material and not too detailed, requiring a lot of presentation. practical examples, and want feedback and evaluation. Needs analysis showed that learners are more interested in grammar studies that focus on I'rob. In the resource analysis, the results of the identification of the feasibility of using a smartphone camera as a video recording device, Filmora as a video editing application and a Wordwall quiz application as an evaluation medium were obtained. The design produced by this lesson has a duration of 20 minutes accompanied by enrichment of applicable examples and a test link is available for evaluation materials. in the process of implementing products that are ready to be uploaded on Youtube so that they can be accessed in general. Learning evaluation is based on the number of viewers, comments, and scores on the available test links. The results of this study can be a reference for Arabic learning activists in designing online learning.